MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI MELIPAT KERTAS ORIGAMI UNTUK ANAK TUNADAKSA TIPE POLIOMYELITIS - Irma - Zulvia (Jurnal Penelitian Pendidikan Khusus, 2014)
This research is backgrounded by a problem was found with a kid in physical disability poliomyelitic type in first class of 1 C D1 has abnormalities in soft motor. After setting  an assessment knowing that kid could not able in writing and hold a pen rightly. The reseacher tried to help the kid to increase ability of soft motoric through folding origami paper. This research aim to increase ability of soft motor in physical disability kid of poliomyelity type of 1C D1 class in SLB Fan Redha Padang. Using Single Subject Research (SSR) type with A-B design. Where A condition was baseline with beginning kid ability in soft motor. Before giving treatment B condition was intervention where kid was given a treatment through folding origami paper. Result of this research looked that ability of soft motor of disability kid of poliomyelity type in 1C D1 class of Fan Redha Padang increase after given intervention through fold the origami paper. At baseline condition done during six times observasion the kid did not do anything ordred by researcher to that the kid had 0% score. At intervention condition done during fifteen time observation in kid ability. With at beginning increasing and then decline and increase more so that at the and meeting and the kid had highest score at 100%. Persentage of overlape at baseline condition (A) with condition in 0%. So  this research proved that formula of the problem as shown before had answered that folding origami paper. Can increare ability of soft motor in physical disability kid poliomyelitis type X 1C D1 class at SLB Fan Redha Padang. Researcher suggest to the teachers to use origami paper in increasing kid soft motor.